Parathyroid Hormone in Human Plasma: IMMUNOCHEMICAL CHARACTERIZATION AND BIOLOGICAL IMPLICATIONS - Segre, Gino V. (1972)
Antigenic recognition of four anti-bovine parathyroid hormone antisera was characterized by their reactivity with bovine hormonal fragments (1-34, 1-13, 14-34, 19-34, 53-84) and human hormone extracted from parathyroid adenomas. All antisera were found to have antibody populations which recognized more than one antigenic determinant and all antisera differed in their specificity and reactivity for the fragments of bovine hormone. By modification of two antisera, GP-1 and GP-133, by preincubation with excess concentrations of 1-34 or 53-84 fragments, antigenic recognition was restricted to defined regions of the hormonal sequence. When assays using these modified antisera were applied to the study of hormones extracted from glands, greater immunochemical similarities were seen between bovine and human parathyroid hormone using assays that were specific for the measurement of amino-terminal portions of the hormones than of the carboxy-terminal portions. When assays using these antisera were applied to the study of endogenous parathyroid hormone in human plasma, the immunoreactive hormone in the general circulation was shown to substantially lack an amino-terminal portion of the sequence of the intact hormone, including an antigenic determinant requiring all or some of the 14-19 region. This deletion accounts, at least in part, for the immunochemical heterogeneity of plasma parathyroid hormone in man. Radioimmunoassay of fractions of peripheral plasma subjected to gel filtration confirms that the dominant form of the immunoreactive hormone in the general circulation of man is a hormonal fragment that is totally devoid of amino-terminal reactivity. Because of this deletion, it can be concluded that most of the immunoreactive parathyroid hormone in the general circulation of man must be biologically inactive.